Cost-effectiveness analysis of rapid diagnostic tests for G6PD deficiency in patients with Plasmodium vivax malaria in the Brazilian Amazon. (December 2016) - Peixoto, Henry; Brito, Marcelo; Romero, Gustavo; Monteiro, Wuelton; Lacerda, Marcus; Oliveira, Maria
Abstract Background The use of primaquine (PQ) for radical treatment ofPlasmodium vivax in carriers of G6PD deficiency (G6PDd) constitutes the main factor associated with severe haemolysis in G6PDd. The current study aimed to estimate the incremental cost-effectiveness ratio of using a rapid diagnostic test (RDT) to detect G6PDd in male patients withP. vivax malaria in the Brazilian Amazon, in comparison with the routine indicated by the Programme for Malaria Control, which does not include this evaluation. Methods A cost-effectiveness analysis of estimated RDT use was carried out for the Brazilian Amazon for the year 2013, considering the perspective of the Brazilian Public Health System. Using decision trees, estimates were compared for two different RDT strategies for G6PDd in male individuals infected withP. vivax before being prescribed PQ, with the routine indicated in Brazil, which does not include prior diagnosis of G6PDd. The first strategy considered the combined use of RDT BinaxNOW® G6PD (BX-G6PD) in municipalities with more than 100, 000 inhabitants and the routine programme (RP) for the other municipalities. Operational limitations related to the required temperature control and venous blood collection currently restrict the use of RDT BX-G6PD in small municipalities. The second strategy considered the use of the RDT CareStart™ G6PD (CS-G6PD) in 100 % of the municipalities. The analysis was carried out for the outcomes: "adequately diagnosed case" and "hospitalization avoided". Results For the outcome "adequately diagnosed case", comparing the RDT strategies based on RDT with the routine control programme (RP), the CS-G6PD strategy was the most cost-effective, with BX-G6PD extendedly dominating (the ICER of BX-G6PD compared with RP was higher than the ICER of CS-G6PD compared with RP). CS-G6PD dominated the other strategies for the "hospitalization avoided" outcome. Conclusion The CS-G6PD strategy is cost-effective for adequately diagnosing cases and avoiding hospitalization. This information can help in decision-making, both in incorporating prior diagnosis in the use of PQ and to promote greater safety among G6PD deficient individuals in the Brazilian AmazonP. vivax endemic areas.